Analisis Pengaruh Stuktur Modal Terhadap Harga Saham Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Pratiwi, Monica Weni (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This research aims to test the influence of capital structure towards the stock price to the firm size as variable moderation. The population used is company property and real estate sectors listed on the Indonesia stock exchange during the year 2015 to 2017. The sample in this research as much as 78 obtained with the method of purposive sampling. This research uses a quantitative approach with multiple linear regression for hypothesis testing. The test results show that the capital structure has an effect on stock prices, and capital structure has an effect on stock prices moderated by the firm size.